A Survey on Efficient Life Detection System Using Microwave Signal - Swati S. Patil,; Komal Todkar,; Namrata A. Gandhi,; Nilesh M. Verulkar, (Journal of Electronic Design Engineering, 2016)
Thousands of persons killed as a reason behind earthquake. The on top of words is not the headlines of the newspaper, however, such news come back once the disaster destroyed the sector. The disaster within the big apple town at ‘World Trade Center’ claimed lives of quite 5000 individuals. It absolutely was aforementioned if survivors have been found and rescue earlier the numbers of victims are lower. There is without stopping to the amount of lives lost because the results of such disasters as landslides, folded tunnels and avalanches. The microwave life detection system is developed for the search and rescue of victims at bay underneath the dust of folded building throughout the earthquake or different disasters. The projected system utilizes L-band frequency that is ready to notice metabolic process and heart fluctuations. The operation principle relies on physicist frequency shift of the radiation mirrored from the buried victim. The schematic diagram of microwave Transmitting/Receiving (T/R) and litter cancellation scheme square measure enclosed during this report. During this report varied components of a microwave life detection system like antenna, directional mechanical device, and splitter has been mentioned. By advent of this technique the planet death rate as a reason behind an earthquake might decrease to larger extent.